Ukraine war: A war of languages and bodies - Meylahn, Johann-Albrecht (HTS teologiese studies, 2022)
For most readers, myself included, the views and opinions on the Russian attack and consequent war in Ukraine are dependent on the main media houses, who present the situation in a certain language. In this article, Badiou’s understanding of democratic materialism (languages and bodies) will be explored within the context of the war, and how language is used to order bodies into categories of good and evil. In democratic materialism, there are only bodies and languages, but no truth. The question that will be explored in these few pages is, is there a way beyond democratic materialism via truth towards a materialist dialectic?Contribution: The paper contributes to the current discussion on the war in Ukraine and tries to make sense of the geopolitical context of the war. It then seeks to engage with these discourses from a theological perspective.